Aging and the effects of emotion on cognition: Implications for psychological interventions for depression and anxiety. Issue 1 (30th January 2015) - Knight, Bob G.; Durbin, Kelly
Abstract: We review findings from laboratory research on age differences in the effects of emotion on cognition. Particular attention is given to sadness leading to mood congruent memory and to anxiety leading to selective attention bias to threat. While older adults in normal moods show the positivity effect as expected from socio‐emotional selectivity theory, older adults whose mood has changed from baseline to sad or anxious show these mood‐related cognitive biases. These mood‐related biases are a foundational part of the theory underlying cognitive behavior therapy (CBT) and so these laboratory findings suggest ways that CBT may work differently with older adults. Pilot work suggests that the presence or absence of these effects may also predict responsiveness to treatment using CBT.